Kekerasan Dalam Rumah Tangga Pada Film Bolehkah Sekali Saja Kumenangis 2024: Analisis Wacana Kritis Model Van Dijk - Annisa Zahrani Fahira Naafita Sari; Syafrida Nurrachmi Febriyanti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The issue of domestic violence in Indonesia has a high number of cases, so it is often raised in a film. This study analyzes the discourse of domestic violence in the film "Bolehkah Sekali Saja Kumenangis (2024)" using Teun A. Van Dijk's critical discourse analysis (qualitative descriptive), with data from documentation, filmmaker interviews, and literature studies. The results on the text dimension show the patriarchy of perpetrators and cycles of violence, as well as the diverse responses and impacts of victims, ranging from passive to active resistance to breaking the chain of violence. The dimension of social cognition reveals the influence of social cognition, ranging from voicing issues, presenting heroes, to patriarchal culture. The social context dimension links the film to the reality of domestic violence in Indonesia, such as high unreported cases and reporting barriers (stigma, patriarchy, isolation, cycle of violence). This film discusses the importance of women's awareness and courage against domestic violence.